Towards the neurobiology of chronic pain - Carli, Giancarlo; Zimmermann, Manfred (Progress in brain research, 1996)
This excellent volume provides a well-balanced review of activity-dependent modifications of synaptic efficacy which follow noxious events, and is based on the symposium "Towards the Neurobiology of Chronic Pain", organized in Siena, at the Certosa di Pontignano. The book will contribute to the continuing interest in understanding pain reinforcement by the brain. This emerging new concept can in turn be expected to have a great impact on the development of clinical paradigms of pain prevention and rehabilitation
Includes bibliographical references and index
Gesehen am 03.05.2021
Keywords: Konferenzschrift -- 1994 -- Siena